VKOR variant and sex are the main influencing factors on bromadiolone tolerance of the house mouse (Mus musculus L.). Issue 3 (13th May 2015) - Šćepović, Tanja; Jokić, Goran; Esther, Alexandra; Kataranovski, Dragan; Vukša, Petar; Đedović, Suzana; Vukša, Marina
Abstract: BACKGROUND: After reports of management problems in practice, a survey was conducted to determine the presence of bromadiolone‐resistant animals in different house mouse ( Mus musculus L.) populations in Serbia. A 21 day no‐choice feeding test was carried out to examine the resistance of house mice to bromadiolone. Eighty house mice collected from four locations (ten males and ten females per location) were tested for bromadiolone tolerance. Surviving animals and their F1 offspring were screened for mutations. The influence of VKOR variant, zygosity and sex on bromadiolone tolerance was analysed. RESULTS: Bait intake and changes in body weight revealed different animal responses regarding susceptibility or resistance. Leu128Ser, Tyr139Cys and a new Ala21Thr polymorphism were detected in wild‐born survivors and their F1 generation. However, not every individual with the polymorphisms Leu128Ser and Tyr139Cys survived the feeding test. VKOR variants and sex caused variations in bromadiolone tolerance. CONCLUSION: For the first time it was shown that the VKOR variant, along with sex, is responsible for bromadiolone tolerance in house mice. Other factors influencing bromadiolone tolerance, including sex‐specific factors, cannot be excluded. The tolerance levels of VKOR variants should be determined in further studies in order to evaluate the effectiveness of bromadiolone in sustainable management. © 2015 Society of Chemical Industry